Involvement of apoptosis in the protective effects of Dracocephalum moldavaica in cerebral ischemia reperfusion rat model. Issue 19 (2nd October 2019) - Wu, Peng; Yan, Xu-Sheng; Zhou, Li-Li; Liu, Xin-Lang; Huo, Dong-Sheng; Song, Wei; Fang, Xin; Wang, He; Yang, Zhan-Jun; Jia, Jian-Xin
ABSTRACT: An extract of Dracocephalum moldevica (DML) was found to exert protective effects on cerebral ischemia-reperfusion injury (CIRI); however, the mechanisms underlying the observed actions of this plant-derived mixture remain to be determined. Thus, the aim of this study was to examine the influence of DML on CIRI rat model induced by middle cerebral artery occlusion (MCAO). The following parameters were measured: (1) viable neurons in the infarcted area using Nissl staining; and (2) immunohistochemistry and Western blot were employed to determine protein expression levels of p53, bcl-2 associated X protein (bax) and B-cell lymphoma-2 (bcl-2), three biomarkers of apoptosis. MCAO significantly decreased the number of viable cortical pyramidal neurons in the infarcted area, while treatment with DML extract significantly elevated the number of viable neurons. MCAO was found to significantly elevate in gene expression levels of p53 and protein expression levels bax accompanied by diminished protein expression levels of bcl-2. Prior administration of DML extract produced marked reduction in gene expression levels of p53 and protein expression levels bax but increased in protein expression levels of bcl-2. Data suggested apoptosis was initiated in MCAO and that DML was effective in treating CIRI via an anti-apoptotic action as evidenced by inhibition of gene expression levels of p53 and protein expression levels of bax with concomitant elevation in protein expression levels of bcl-2. Our findings suggest that extract of DML may prove beneficial in treatment of cerebrovascular disorders.